1993
DOI: 10.1159/000175993
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Single Oral Dose of Aspirin on Human Platelet Functions and Plasma Plasminogen Activator Inhibitor-1

Abstract: Previous reports documented the inhibitory efficacy of different doses of aspirin on arachidonic acid (AA)-induced platelet aggregation, however, the sensitivity of platelets toward other agonists as well as the effects of aspirin on platelet and plasma plasminogen activator inhibitor-1 (PAI-1) release and levels were not investigated. Hence, the present study was undertaken to investigate the effect and duration of action of a single oral dose (650 mg) of aspirin on human platelet functions (n = 34, normal he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 9 publications
2
16
0
2
Order By: Relevance
“…We present data showing that rectal administration of aspirin (200-mg suppositories) also suppressed platelet aggregation very quickly within 30 min and that the suppression continued for 24 h. Our results are consistent with those for oral aspirin showing that aggregation remained suppressed for 48 h after the start of aspirin administration [7, 8]. This long-lasting suppression by aspirin makes it possible for it to be given on a once-a-day basis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We present data showing that rectal administration of aspirin (200-mg suppositories) also suppressed platelet aggregation very quickly within 30 min and that the suppression continued for 24 h. Our results are consistent with those for oral aspirin showing that aggregation remained suppressed for 48 h after the start of aspirin administration [7, 8]. This long-lasting suppression by aspirin makes it possible for it to be given on a once-a-day basis.…”
Section: Discussionsupporting
confidence: 88%
“…Oral administration of aspirin suppresses platelet aggregation very quickly within 15 [7]to 120 min [8]. We present data showing that rectal administration of aspirin (200-mg suppositories) also suppressed platelet aggregation very quickly within 30 min and that the suppression continued for 24 h. Our results are consistent with those for oral aspirin showing that aggregation remained suppressed for 48 h after the start of aspirin administration [7, 8].…”
Section: Discussionsupporting
confidence: 87%
“…In 1990, urinary excretion of both 6-keto-prostaglandin F1␣ and thromboxane B2 were found elevated 2 weeks after aspirin was stopped (Vial et al, 1991). Three years later, Mousa et al (1993) showed that although platelets are inhibited by a single dose of aspirin, 6 days after the dose, fibrinogen binding to activated platelets was increased over baseline as was arachidonic acid-induced platelet aggregation. In 1996, the effect of aspirin discontinuation on fibrin-fibrinogen was shown (Fatah et al, 1996).…”
Section: Aspirinmentioning
confidence: 99%
“…However, early spontaneous recanalization of an extracranial arterial occlusion (especially an IA occlusion) has rarely been reported. of aspirin administration, whereas an increased thromboembolic effect appears at eight to ten days after drug cessation due to new platelet formation with increased COX-1 activity and rebound inflammation (9)(10)(11). The studies of Sibon and Orgogozo (12) and Maulaz et al (13), have demonstrated that recent aspirin discontinuation is associated with increased stroke risk, with most strokes occurring between six and 10 days after aspirin cessation.…”
Section: Discussionmentioning
confidence: 99%